2020
DOI: 10.33073/pjm-2020-046
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Production Potential of Salmonella Serovars Isolated from Chickens in North West Province, South Africa

Abstract: Bacterial biofilms have recently gained considerable interest in the food production and medical industries due to their ability to resist destruction by disinfectants and other antimicrobials. Biofilms are extracellular polymer matrices that may enhance the survival of pathogens even when exposed to environmental stress. The effect of incubation temperatures (25°C, 37°C, and 40°C) and Salmonella serotype on biofilm-forming potentials was evaluated. Previously typed Salmonella serotypes (55) isolated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(68 reference statements)
2
2
0
Order By: Relevance
“…Half of the serotypes in our study were able to form biofilm with varied adhesion strengths (Table 3). This result corroborates the results of recent studies that show Salmonella serotypes are capable of producing biofilms with various intensities (Díez-García et al 2012, Akinola et al 2020. The variety of strains can be seen as the reason for the difference in the ability of biofilm formation (Kalai Chelvam et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Half of the serotypes in our study were able to form biofilm with varied adhesion strengths (Table 3). This result corroborates the results of recent studies that show Salmonella serotypes are capable of producing biofilms with various intensities (Díez-García et al 2012, Akinola et al 2020. The variety of strains can be seen as the reason for the difference in the ability of biofilm formation (Kalai Chelvam et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Biofilm forming bacteria contribute to many microbial infections. The ability of different Salmonella serotypes to produce biofilm has been reported in several studies (Silva et al 2019, Akinola et al 2020. Half of the serotypes in our study were able to form biofilm with varied adhesion strengths (Table 3).…”
Section: Discussionsupporting
confidence: 70%
“…Similar to our results, 62% of S. Enteritidis and 73.8% of S. Typhimurium isolates from avian sources exhibited the ability to form biofilms, with S. Enteritidis demonstrating a strong capacity for adhesion [ 72 ]. Among Salmonella isolated from chickens in South Africa, the proportion of isolates producing biofilms at different temperatures reached 86.44–88.14%, and S. Heidelberg and S. Weltevreden were the serovars with the highest biofilm-forming capacities [ 73 ]. Another study found that all of the Salmonella serovars were isolated from meat, with 75.86% exhibiting moderate biofilm formation and 24.14% displaying strong biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al [ 75 ] believed that S. Gallinarum and S. Minnesota had stronger biofilm production abilities than the S. Enteritidis, S. Typhimurium, and S. Heidelberg serovars. However, the impact of incubation temperature on biofilm formation was found to be more significant than that of the serovar [ 72 , 73 ]. The results of different studies indicated that the differences in biofilm production ability might be more related to the source, region, and characteristics of the isolates themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Salmonella spp. has been linked as the causative agent for foodborne illness in many cases in recent years (Akinola et al, 2020), and the formation of biofilm on food contact surfaces certainly contributes to cross-contamination and increases the risk of a foodborne outbreak (Lee et al, 2020). Therefore, many studies were conducted to identify the characteristics of biofilm and the effectiveness of disinfectants on it.…”
Section: Introductionmentioning
confidence: 99%